2004
DOI: 10.1103/physrevd.70.124002
|View full text |Cite
|
Sign up to set email alerts
|

Stationary and axisymmetric solutions of higher-dimensional general relativity

Abstract: We study stationary and axisymmetric solutions of General Relativity, i.e. pure gravity, in four or higher dimensions. D-dimensional stationary and axisymmetric solutions are defined as having D − 2 commuting Killing vector fields. We derive a canonical form of the metric for such solutions that effectively reduces the Einstein equations to a differential equation on an axisymmetric D − 2 by D − 2 matrix field living in three-dimensional flat space (apart from a subclass of solutions that instead reduce to a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
477
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(485 citation statements)
references
References 24 publications
6
477
0
2
Order By: Relevance
“…For this computation, group rotation is sufficient, but we expect that in more complicated situations, in particular for configurations involving three or more poles, one needs to develop some other algorithmic techniques to find appropriate vectors. In this regard, ideas from the interval structure [26][27][28] of gravitational solutions can be useful, but at the moment this remains an open challenging problem.…”
Section: Jhep03(2014)101 6 Discussionmentioning
confidence: 99%
“…For this computation, group rotation is sufficient, but we expect that in more complicated situations, in particular for configurations involving three or more poles, one needs to develop some other algorithmic techniques to find appropriate vectors. In this regard, ideas from the interval structure [26][27][28] of gravitational solutions can be useful, but at the moment this remains an open challenging problem.…”
Section: Jhep03(2014)101 6 Discussionmentioning
confidence: 99%
“…This solution has symmetry group R × U(1) and hence qualifies as Weyl-Papapetrou (a stationary axisymmetric vacuum solution) [35,30,36]. Setting…”
Section: S-dihole and Kerr Black Hole Card Diagramsmentioning
confidence: 99%
“…3 Spherical prolate coordinates are a special case of C-metric coordinates; see [29,30] and references therein. Our spherical prolate diagrams are analogs of C-metric diagrams in [31].…”
Section: Singularity Locus and Affine Coordinatesmentioning
confidence: 99%
“…As an example we note the generalized Weyl ansatz [24,25] for static and stationary solutions with D − 2 commuting Killing vectors, in which the Einstein equations simplify considerably. For the static case, this ansatz is for example relevant for bubble-black hole sequences [49] in five and six-dimensional KK space.…”
Section: Overview Of Solution Methodsmentioning
confidence: 99%
“…Here, it has been found that in addition to the Myers-Perry (MP) black holes [15], there exist rotating black rings [16,2] and multi-black hole solutions like black-Saturns and multi-black rings [17,18,19,20] including those with two independent angular momenta [21,22,23]. All of these are exact solutions which have been obtained with the aid of special ansätze [24,25] based on symmetries and inverse-scattering techniques [26,27,28,29]. We refer in particular to the review [2] for further details on the black ring in five dimensions and Ref.…”
Section: Introductionmentioning
confidence: 99%